Bonnie's new old outfit - Moore, Madison, 1997- (Albert Whitman & Company, 2022)
Bonnie wants the perfect first-day-of-school outfit, but everything in her wardrobe is too big or too small or worn out, so with the help of her family, Bonnie learns to use maker techniques like embroidery, knitting, and natural dyes to turn her old clothes into something new and original.